Indoor environmental quality index for conservation environments: The importance of including particulate matter. (December 2017) - Marchetti, Andrea; Pilehvar, Sanaz; 't Hart, Lucy; Leyva Pernia, Diana; Voet, Olivier; Anaf, Willemien; Nuyts, Gert; Otten, Elke; Demeyer, Serge; Schalm, Olivier; De Wael, Karolien
Abstract: It is commonly known that the conservation state of works of arts exhibited inside museums is strongly influenced by the indoor environmental quality (IEQ). Heritage institutions traditionally record and evaluate their IEQ by monitoring temperature, relative humidity, and -more rarely-light. However, smart use of technology enables monitoring other parameters that give a more complete insight in environmental 'air aggressiveness'. One of this parameters is particulate matter (PM) and especially its concentration, size distribution and chemical composition. In this work, we present a selection of data sets which were obtained in a measuring campaign performed in the War Heritage Institute in Brussels, Belgium. A continuous monitoring of PM concentration with a light scattering based particle counter was performed. In addition the daily mass concentration and size distribution of airborne PM was monitored by means of Harvard impactors. The chemical composition of sampled PM was inferred from the results of XRF and IC analysis. The insights from these datasets are combined with the results of traditional environmental monitoring (temperature, relative humidity and light intensity), and assessed against the recommended guidelines for conservation environments. By using an integrated approach based on the calculation of an IEQ-index, we present a straightforward methodology to evaluate and visualize the IEQ including also continuous PM monitoring. It is clear from the results of this study how including PM in IEQ analysis allows to identify potential risks for museum collections that remain invisible when only traditional parameters are considered. Highlights: Significant PM concentrations can be present in conservation environments. Dangerous PM levels are invisible when only traditional parameters are monitored. A method for including continuous PM analysis in IEQ-index calculations is presented.